Problem of Intra- and Postoperative Complications in Cases of Treatment of Acute Calculous Cholecystitis and Ways of Their Prevention - A. V. Bautkin; M. F. Cherkasov; A. A. Eleyev (Медицинский вестник Юга России, 2012)
This review presents the results of the latest Russian and foreign studies concerning the problem of acute cholecystitis and its complications in the modern surgery. This paper reflects the author’s understanding of the factors that play an important role in the development of cholelithiasis and its complications, and the advanced methods of diagnostics and treatment of acute cholecystitis.